Zarządzanie ryzykiem kredytowym przedsiębiorstw z wykorzystaniem metody DEA w ramach credit-scoringu - Feruś, Anna (Managing Companies Credit Risk By Means Of Dea Method Within The Framework Of Credit-Scoring, 2008)
The aim of the article is to present the possibilities of implementing the DEA method in the management of companies' credit risk in the Polish economy environment. What favours the suggessted approach is the fact that in Poland, unlike in western countries, the DEA method has not been implemented in order to define the level of companies' credit risk so far.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 153-160